An explanatory model of attitudinal fear of HIV/AIDS testing in the construction industry. Issue 1 (18th January 2016) - Bowen, Paul; Govender, Rajen; Edwards, Peter; Cattell, Keith
Abstract : Purpose: – Prevalence of HIV/AIDS infection in the South African construction industry exceeds that of most other economic sectors. Voluntary counselling and testing is pivotal in combatting the spread of the disease. Little is known about the attitudinal fear of testing among construction workers, and the determinants thereof. The purpose of this paper is to address these shortcomings. Design/methodology/approach: – A conceptual integrated model of fear of testing is proposed. Demographic characteristics and behavioural and cognitive factors are posited to explain attitudinal fear of testing. Regression analysis and structural equation modelling are used to test the model, using data gathered from 512 site-based participants in a questionnaire survey. Findings: – Prejudice and lifestyle risk are the terminal predictors of fear of testing. Prejudice is determined by education level and HIV/AIDS transmission knowledge. Knowledge is predicted by education level and ethnicity. Lifestyle risk is determined by age, gender, harmful substance use, and knowledge. Harmful substance use is determined by age, gender, ethnicity, and employment type. The inter-relationship between knowledge about HIV/AIDS, prejudice towards HIV+ persons, and fear of testing is complex and nuanced. Practical implications: – Intervention strategies by firms should positively address attitudinal fear of testing. Employers should ensure that effective communication is established with workers. Interventions relating to harmful substance use by employees need particular attention. Awareness campaigns should be sensitive to ethnic and cultural values, and to inter-generational differences. Originality/value: – Harmful substance use and knowledge about HIV/AIDS transmission are indirect predictors of fear of testing. Education and ethnicity are critical dimensions of knowledge. The complex inter-relationship between knowledge, prejudice, lifestyle risk, and fear of testing is highlighted, providing guidelines for intervention management.